AKTIVITAS ANTIOKSIDAN EKSTRAK BUNGA, BATANG, DAN DAUN BROKOLI (BRASSICA OLERACEAE VAR. BOTRYTIS L.) DENGAN METODE DPPH - Syifa Printiarti, Siti
Free radicals are atoms or molecules with one or more unpaired electrons in their outer orbitals, therefore, they need to take electrons from other molecules, which creates an imbalance of other molecules and initiates a chain reaction leading to health problems such as degenerative diseases, cell damage, tissue damage, and cancer. Antioxidants can reduce the negative effects of free radicals. Antioxidant can be found in various plants, such as broccoli ((Brassica oleraceae var. botrytis L.). The research aims to study antioxidant activity of floret, stalk, and leaves extracts of broccoli using DPPH (2,2-diphenyl-1-picrylhydrazyl) method; determine total phenolic and flavonoid content. The floret, stalk, and leaves of broccoli were extracted by reflux method using increasing polarity solvent, e.g. nhexane, ethyl acetate, and ethanol. Determination of percentage DPPH scavenging activity, total phenolic and flavonoid content were performed by UV-visible spectrophotometry. The result of phytochemical screening showed that crude drug of broccoli’s floret, stalk, and leaves contained flavonoid, phenol, tannin, and steroid/triterpenoid. Total phenolic compounds of ethanol extract from floret, stalk, and leaves are 0,91 ± 0,05 g GAE/100 g, 1,02 ± 0,05 g GAE/100 g respectivelyand 0,99 ± 0,08 g GAE/100 g. Total phenolic compounds of ethyl acetate extract from floret, stalk, and leaves are 2,58 ± 0,13 g GAE/100 g, 1,8 ± 0,15 g GAE/100 grespectively, and 1,93 ± 0,15 g GAE/100 g. Total phenolic compound of n-hexane extract from floret, stalk, and leaves are 1,6 ± 0,09 g GAE/100 g, 1,4 ± 0,02 g GAE/100 g respectively, and 2,76 ± 0,08 g GAE/100 g. Total flavonoid compound ofethanol extract floret, stalk, and leaves; ethyl acetate extract from floret, stalk, and leaves; n-hexane extract from floret, stalk, and leavesare 0,56 ± 0,05 g QE/100 g, 0,25 ± 0,02 g QE/100 g, 0,25 ± 0,02 g QE/100 g; 0,87 ± 0,07 g QE/100 g, 1,09 ± 0,10 g QE/100 g, 1,52 ± 0,09 g QE/100 g; 0,28 ± 0,02 g QE/100 g, 0,31 ± 0,03 g QE/100 g, 0,88 ± 0,07 g QE/100 g. Ethanol leaves extract of broccoli had the highest total phenolic content (2.76 ± 0.08 g GAE/100 g). Meanwhile, ethyl acetate leaves extract of broccoli gave the highest total flavonoid content (1.52 ± 0.09 g QE/100 g).The percentage of DPPH 50 µg/mL scavenging activity of ethanol extract floret, stalk, and leaves; ethyl acetate extract from floret, stalk, and leaves; n-hexane extract from floret, stalk, and leavesare 58,73 ± 4,84%, 63,45 ± 4,84%, 68,19 ± 0,71%; 74,19 ± 2,25%, 63,91 ± 1,59%, 61,92 ± 1,02%; 68,66 ± 1,26%, 73,55 ± 3,53%, 72,08 ± 2,92%. As for the DPPH 50µg/mL scavenging activity of ascorbic acid as a comparison is 96.93 ± 0.97%. The result indicated that ethyl acetate floret extract of broccoli 50 µg/mL showed the highest percentage of DPPH 50 µg/mL scavenging activity (74.19 ± 2.25%). This close comparison showed that floret, stalk and leaves extracts of broccoli were potential to be developed as source of natural antioxidant.